2011
DOI: 10.1002/hbm.21030
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of resting state EEG in the developing young brain: Structure comes with maturation

Abstract: During childhood, brain structure and function changes substantially. Recently, graph theory has been introduced to model connectivity in the brain. Small-world networks, such as the brain, combine optimal properties of both ordered and random networks, i.e., high clustering and short path lengths. We used graph theoretical concepts to examine changes in functional brain networks during normal development in young children. Resting-state eyes-closed electroencephalography (EEG) was recorded (14 channels) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
158
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(180 citation statements)
references
References 71 publications
18
158
2
2
Order By: Relevance
“…In those studies where connectivity data or conventional graph analysis showed an effect, an effect was always present in the MST analysis as well (Boersma et al, 2011;2013;Olde Dubbelink et al, 2013;van Dellen et al, 2013). In other studies MST analyses succeed in demonstrating an experimental effect while other methods were less successful (Demuru et al, 2013;Lee et al, 2006).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 89%
See 2 more Smart Citations
“…In those studies where connectivity data or conventional graph analysis showed an effect, an effect was always present in the MST analysis as well (Boersma et al, 2011;2013;Olde Dubbelink et al, 2013;van Dellen et al, 2013). In other studies MST analyses succeed in demonstrating an experimental effect while other methods were less successful (Demuru et al, 2013;Lee et al, 2006).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 89%
“…If we compare this pattern to the change observed between age 5 and age 7, one could argue that brain networks in girls show a more mature pattern. The same EEG dataset has been analysed before with more classical graph theoretical techniques (Boersma et al, 2011), showing that the clustering coefficient increased in the alpha band, and the path length in all bands, between age 5 and 7. Clustering was higher in girls compared to girls in the alpha and beta bands.…”
Section: More Extensive Characterization Of the Mst In Eeg Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, the long distant connections (edges) are weak in contrast with stronger short-distance edges. During development, short-distance connections weaken, while the long-distance connections increase in strength [46][47][48][49] . The SWN architecture already exists in the 1st month of life [48] and this organization seems to assume higher values in adults [50] .…”
Section: Normal Brain Network Organizationmentioning
confidence: 99%
“…Second, increasing numbers of pair-wise synchrony estimates poses a statistical challenge due to multiple comparisons, and needs solutions akin to those used in neuroimaging (McIntosh and Mišic, 2013;Singh et al, 2011;Singh and Phillips, 2010). Recently introduced graph measures, especially those based on weighted and surrogate-normalized matrices (Boersma et al, 2011;Rubinov and Sporns, 2010), may effectively mitigate the challenge associated with massive pairwise comparisons and the underlying assumptions of temporal stationarity and inter-individual similarity (Sporns, 2013).…”
Section: Effects Of Increasing Electrode Numbersmentioning
confidence: 99%